2023
DOI: 10.1111/bjh.18891
|View full text |Cite
|
Sign up to set email alerts
|

Elevated erythroferrone distinguishes erythrocytosis with inherited defects in oxygen‐sensing pathway from primary familial and congenital polycythaemia

Abstract: Congenital erythrocytoses represent a heterogenous group of rare defects of erythropoiesis characterized by elevated erythrocyte mass. We performed molecular‐genetic analysis of 21 Czech patients with congenital erythrocytosis and assessed the mutual link between chronic erythrocyte overproduction and iron homoeostasis. Causative mutations in erythropoietin receptor (EPOR), hypoxia‐inducible factor 2 alpha (HIF2A) or Von Hippel–Lindau (VHL) genes were detected in nine patients, including a novel p.A421Cfs*4 EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…For example, it regulates stem cell fate determination (Sugimoto et al, 2017;Qiu et al, 2023), cell proliferation and differentiation (He et al, 2018), skeletal muscle development and repair (Bernareggi et al, 2022), vascular endothelial cell permeability (Friedrich et al, 2019), and tumor cell invasion and metastasis (Jiang et al, 2022). It has also been found that Piezo1 mutations are also associated with several diseases, such as congenital erythrocytosis (Knight et al, 2019;Filser et al, 2021;Sochorcova et al, 2023) and familial pulmonary hypertension (Wang Z. et al, 2021;Liao et al, 2021;Porto Ribeiro et al, 2022). Currently, there are also a large number of studies that have identified a potential relationship between Piezo1 and fibrotic diseases (Zhang et al, 2021a;Braidotti et al, 2022a;He et al, 2022a;Swain et al, 2022).…”
Section: Introduction Of Piezo1mentioning
confidence: 99%
“…For example, it regulates stem cell fate determination (Sugimoto et al, 2017;Qiu et al, 2023), cell proliferation and differentiation (He et al, 2018), skeletal muscle development and repair (Bernareggi et al, 2022), vascular endothelial cell permeability (Friedrich et al, 2019), and tumor cell invasion and metastasis (Jiang et al, 2022). It has also been found that Piezo1 mutations are also associated with several diseases, such as congenital erythrocytosis (Knight et al, 2019;Filser et al, 2021;Sochorcova et al, 2023) and familial pulmonary hypertension (Wang Z. et al, 2021;Liao et al, 2021;Porto Ribeiro et al, 2022). Currently, there are also a large number of studies that have identified a potential relationship between Piezo1 and fibrotic diseases (Zhang et al, 2021a;Braidotti et al, 2022a;He et al, 2022a;Swain et al, 2022).…”
Section: Introduction Of Piezo1mentioning
confidence: 99%